THE MODERN METHODS OF THE SPEECH SIGNAL ANALYSIS - Щербак, Л. М.; Литвиненко, Ю. В.; Погрібна, Ю. В. (Science-based technologies, 2009)
The modern methods of the analysis in information technologies of transfer of the information are considered.The basic methods of coding of a speech signal, and also methods of synthesis of a speech signal are given.